Novel Topical Application of a Postbiotic, LactoSporin®, in Mild to Moderate Acne: A Randomized, Comparative Clinical Study to Evaluate its Efficacy, Tolerability and Safety - Muhammed Majeed (Cosmetics, 2020)
Acne vulgaris is a common skin disorder of pilosebaceous units. The therapy for mild-to-moderate acne includes topical antibiotics, benzoyl peroxide and retinoids. In this open-label, randomized monocentric study, we compared the efficacy of LactoSporin® 2% w/w cream with benzoyl peroxide in 64 male and female subjects with mild-to-moderate acne for three weeks. The efficacy parameters were evaluated based on the dermatologist visual assessment and instrumental measurements using Sebumeter® MPA580, Antera 3DTM and VISIA CR 2.2 and subject self-assessment questionnaires. Adverse events were recorded throughout the study period. In order to understand the mechanism of action and properties of LactoSporin, the pH stability, thermostability, antimicrobial activity and 5-alpha reductase activity were evaluated in vitro. A significant improvement was observed in the dermatological assessment of closed comedones (p < 0.0001), open comedones (p = 0.0069) and papules count (p < 0.0001) in comparison to the baseline in both LactoSporin and benzoyl peroxide groups. The antera analysis showed significant improvement in redness (p < 0.0001) and elevation (p < 0.0001) (small and medium) in both the treatment groups. The sebumeter analysis showed a significant decrease in sebaceous secretion (p < 0.0001) for LactoSporin, which resulted in reduced oiliness, pimples, acne spots and redness around the acne spot. The product was found to be safe without any irritancy. LactoSporin was stable at an acidic pH and temperature range of 70 to 90 °C, with antimicrobial activity against various pathogenic bacteria, including Cutibacterium acnes. It was also a potent inhibitor of 5-alpha reductase activity. Thus, it can be concluded that the efficacy of LactoSporin is equivalent to benzoyl peroxide in the treatment of mild-to-moderate acne lesions and better than benzoyl peroxide for reducing the sebaceous secretion and oily, greasy nature of the skin, implying its efficacy in other sebohorriec conditions.